Microwave surface resistance measurements of air-atomised spray deposited Tl-Ba-Ca-Cu-O thick films - Jenkins, A; Su, L; Kale, K; Goringe, M; Burgoyne, J; Dew-Hughes, D; Grovenor, C (IEEE, 1995)
The surface resistance (Rs) of spray pyrolysed Tl2Ba2Ca2Cu3Ox thick films on 1 inch diameter finely polished yttria-stabilized zirconia disks has been measured using a TE011 mode end-wall-replacement cavity at 20 GHz and 77 K. Rs values of 5.3 mΩ and 1.3 mΩ at 20 GHz and 10 GHz (scaled assuming an f2 dependence) respectively were obtained. These results are the best recorded Rs values to date for thick films of any superconductor at the same frequencies and at 77 K. Transport critical current density (Jc) measurements on the films exhibited values of > 3×104 A/cm2 at 77 K.